Intensive lowering of systolic blood pressure to a target of less than 120 mm Hg has no effect on the rate of fatal and non-fatal major cardiovascular events in high-risk patients with type 2 diabetes. Issue 5 (28th July 2010) - Chugh, Atul; Bakris, George
Abstract : Commentary on: Cushman WC Evans GW Byington RP .; ACCORD Study Group . Effects of intensive blood-pressure control in type 2 diabetes mellitus . N Engl J Med 2010 ;362 :1575 –85 .